RAZVOJ PRERAĐENIH MESNIH PROIZVODA SA MALO MASTI I MALO SOLI - Mourtzinos, Ioannis (Journal on Processing and Energy in Agriculture, 2020)
There is a growing demand for the development of healthier meat products with reduced fat and salt. The present study was carried out to develop low fat – low salt processed meat products like sausages. Products were formulated with different fat contents (10% - 20%) and levels of NaCl substitution with KCl (0% - 50%). Physicochemical characteristics and textural attributes were assessed instrumentally, while sensory attributes were determined using Quantitative Descriptive Analysis and Principal Component Analysis. The instrumental analysis showed significant (p <0.05) differences in hardness, brittleness, cohesiveness and chewiness among different sausage formulations. However, sensory analysis did not detect any textural changes due to salt substitution or fat reduction. The product with the highest fat content and KCl substitution was found to have the highest rating of perceived bitterness. The research findings identified the significant interaction between the addition of KCl and the fat content on bitterness perception